Psychological and attitudinal assessment of patients with Fibromyalgia undergoing antalgic management: a short report - Eleonora Balzani; Andrea Fanelli; Ilaria Tarricone; Roberto Muratori; Manuela Campesato; Carmela Tatiana Picone; Rita Maria Melotti (Open Journal of Pain Medicine - Peertechz Publications, 2022)
Objectives: Fibromyalgia (FM) is a widespread condition that is difficult to manage medically. Often algologists are faced with patients who are poorly compliant with pharmacological treatment or with concomitant mood problems. There are treatments tailored to temperament and character patterns. In this study using the division into pain persistence and pain avoidance patterns, a stratification was hypothesized to facilitate its medical management using self-administered questionnaires.  Methods: We screened the population consisting of FM patients to four different questionnaires, namely the Temperament and Character Inventory (TCI), Hospital Anxiety and Depression Scale, Short form 36 and the INTERMED- Self Assessment. Results: A total of thirty-two patients were enrolled. The analyzed population showed preponderant pain avoidance characteristics (90.7%). The persistence pattern proved to be present in only 9.3% of the population. The FM patients examined also reported an incidence of anxiety disorder of 71.9% and depressive disorder of 75%. Conclusion: Dividing the population with FM into patterns yielded uniform results. This justifies a multidisciplinary approach in these FM patients. The high incidence of anxiety and depression from the test results is an outcome that suggests the adoption of the HADS tool in the antalgic evaluation of FM patients.